Don Melchor Carlos Inca, the mestizo Inca : The Carlos Inca in the seventeenth century of Cusco society - Amado Gonzales, Donato (2019)
In 1539, don Cristobal Paullo, one of the sons of the Inca ruler Huayna Capac, was named «Inca» as a political strategy of the Spaniards. Since then, he received an encomienda. Don Cristobal was married to doña Catalina Tocto Oxica and had two sons, don Carlos Inquill Topa and don Felipe Inquill Topa. Don Carlos Inquil Topa married doña Maria Esquivel Amarilla and had only one son named Melchor Carlos Inca. The birth of Melchor was seen by the native population as a great event because an “Inca king” had been born, he even became feared by the colonial Spanish officials when they knew he was referred as the «Capac Inca». Don Melchor Carlos Inca identified himself as grandson of don Cristobal Paullo Inca and great-grandson of the Inca Huayna Capac. He became an important figure within the Cuzco›s colonial society. Don Melchor was baptized and married doña Leonor Arias Carrasco, daughter of the Spanish conquistador Pedro Alonso Carrasco, both events were meaningful for Cusco society. Don Melchors’ encomienda of Pichigua was of great economic and social importance, in order to maintain this encomienda and his social/political activities, he had to sell or mortgage part of his inherited patrimony. In 1599, the Viceroy Luis de Velasco ordered captain Antonio Pereira («regidor perpetuo») to ascertain the ancestry and services of don Mechor and his ancestors. In 1603, don Melchor traveled to Spain in order to claim his privileges and succeeded at obtaining a knighthood in the Order of Santiago. The descendants of Cristóbal Paullo Inca established the Chapel of Our Lady of Guadalupe in the Convent and Church of San Francisco where they had the honour of having a burial vault which was carefully guarded and maintained by their descendants until 17th Century.